2014
DOI: 10.1021/am502335j
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solution Synthesis of Pt–M (M = Fe, Co, Ni) Bimetallic Nanoparticles and Their Catalysis for the Hydrolytic Dehydrogenation of Ammonia Borane

Abstract: Platinum-based bimetallic nanocatalysts have attracted much attention due to their high-efficiency catalytic performance in energy-related applications such as fuel cell and hydrogen storage, for example, the hydrolytic dehydrogenation of ammonia borane (AB). In this work, a simple and green method has been demonstrated to successfully prepare Pt-M (M = Fe, Co, Ni) NPs with tunable composition (nominal Pt/M atomic ratios of 4:1, 1:1, and 1:4) in aqueous solution under mild conditions. All Pt-M NPs with a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 51 publications
4
69
0
Order By: Relevance
“…[32][33][34] Moreover, these processes have been used widely as adequate model reactions to study the catalytic properties of novel catalysts. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The prepared CuNi supported nanocatalysts were first tested for the catalytic hydrolysis of AB to generate H 2 at 25-40 o C. Figure 4a shows the plots of mass activity and apparent activation energy calculated according to Arrhenius equation ( Figure S3) for AB hydrolysis catalyzed by CuNi/MCNS nanocatalysts as a function of the composition. It can be observed that the activity of the catalysts strongly depends on the Cu-Ni composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Moreover, these processes have been used widely as adequate model reactions to study the catalytic properties of novel catalysts. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The prepared CuNi supported nanocatalysts were first tested for the catalytic hydrolysis of AB to generate H 2 at 25-40 o C. Figure 4a shows the plots of mass activity and apparent activation energy calculated according to Arrhenius equation ( Figure S3) for AB hydrolysis catalyzed by CuNi/MCNS nanocatalysts as a function of the composition. It can be observed that the activity of the catalysts strongly depends on the Cu-Ni composition.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] Among the potential candidates for effective chemical hydrogen storage, ammonia borane (AB; NH 3 BH 3 ) and hydrous hydrazine (N 2 H 4 .H 2 O) with high hydrogen contents have been shown to be promising hydrogen carriers for storage and transportation. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Binary metallic nanocatalysts based on the combination of noble and non-noble metals have been widely investigated for hydrogen release from both AB and hydrazine. [35][36][37][38][39][40] Although noble metal-based catalysts have been shown to be effective in these reactions, the high cost hinders their widespread application, so that there is considerable current efforts devoted to explore efficient alternatives based on non-noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…REVIEW plasticized as indicated by increased breaking strain and decreased Young's modulus, Figure 18. 84 Electrical SMP conductivity has been proposed for biomedical 122 and industrial 123 neat SMP actuators stimulated by electric joule heating. Conductive SMPs have also demonstrated enhanced proliferation and osteogenic differentiation of C2C12 cells when compared to nonconductive substrates.…”
Section: Figure 17mentioning
confidence: 99%
“…Ni@Ru coreeshell nanoparticles [4], NieRu alloy nanoparticles [5], RuCo and RuCu on ɤ-Al 2 O 3 [6], RuCu on graphene [7], Ru@Ni coreeshell nanoparticles [8], CueNi on MCM-41 [9], Ru@Co on graphene [10], CoNi@rGO [11], CuCo@MOF nanoparticles [12], Ni/Pt hollow nanospheres [13], Ag/Pd@nanofiber nanoparticles [14], Pt-M (M ¼ Fe, Co, Ni) nanoparticles [15], AuCo@MOF nanoparticles [16], PteCo@GO nanoparticles [17], NiPd@rGO nanoparticles [18], CuNi nanoparticles [19], and Cu@Co on rGO nanoparticles [20] are the examples of those type of catalysts. Very recently, poly(N-vinyl-2-pyrrolidone (PVP))-protected bimetallic nanoparticles, such as rutheniumepalladium [21], platinumeruthenium [22], palladiumerhodium [23], and palladiumeplatinum [24] nanoparticles, have been shown to be highly efficient catalysts for hydrogen generation from boron compounds providing remarkable results.…”
Section: Introductionmentioning
confidence: 99%